Kebenaran tentang menjadi pemimpin/Karen otazo; penerjemah, Ismianto unggu Prakoso;editor Daniel P Purba,Yati Sumiharti - Otazo, Karen; Prakoso, Ismianto unggul; Purba,Daniel P; Sumiharti, Yati (2006)
xix,233 hlm 18 cm